2021
DOI: 10.3390/ani11051339
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Campylobacer jejuni on Swine Processing at a Slaughterhouse in Eastern Spain

Abstract: Campylobacteriosis is the most commonly reported gastrointestinal disease in humans in the EU, mainly from poultry meat consumption. C. jejuni is the main species involved in the human disease. However, little is known about the role of swine meat in its epidemiology. Thus, the aim of this study was to assess the epidemiology and antimicrobial resistance of C. jejuni on swine processing at the slaughterhouse. To this end, a total of 21 pig herds were intensively sampled at the slaughterhouse. Campylobacter iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…These facts point to the consequences of intensive antibiotic application. which promotes intense selection pressure on MDR Campylobacter at the end of slaughter processing, aggravating the problem at the interface of food consumption and human disease [53].…”
Section: Resistance Of Campylobacter Isolatesmentioning
confidence: 99%
“…These facts point to the consequences of intensive antibiotic application. which promotes intense selection pressure on MDR Campylobacter at the end of slaughter processing, aggravating the problem at the interface of food consumption and human disease [53].…”
Section: Resistance Of Campylobacter Isolatesmentioning
confidence: 99%
“…These novel solutions are very useful to farmers as recently it has been reported that cattle and chickens are an important reservoir of campylobacters, associated with human disease, and resistant to erythromycin, ampicillin, tetracycline, nalidixic acid and ciprofloxacin [28]. Measures implemented at the slaughterhouse, rather than at the farm, must also be considered since contamination can also occur in such environments [29]; however, the management involved in farming activities seems to take priority in preventing Campylobacter spp. spreading in livestock [30].…”
Section: Campylobacter Spp Overviewmentioning
confidence: 99%
“…Although the data indicated that most bacteria are still sensitive to individual antimicrobials, the multi-resistance characteristics of foodborne pathogens have been referred to as an important issue [ 173 , 174 ].…”
Section: Surveillance Of Antibiotic Resistance In the Slaughterhousementioning
confidence: 99%